THE EFFECT OF “STORYTELLING USING PUPPET” STRATEGY ON STUDENTS’ SPEAKING ACHIEVEMENT AT EIGHTH GRADE OF JUNIOR HIGH SCHOOL IN SMP NEGERI 1 SERIRIT - Bayu, I. G. B. C.; Piscayanti, K. S.; Paramartha, A. A. G. Y (Universitas Pendidikan Ganesha, 2018)
This study was purposed to investigate whether or not there was a significant effect of storytelling using puppet strategy on students’ speaking achievement at eighth grade of junior high school at SMP N 1 Seririt in the academic year 2018/2019. The research design was Quasi Experimental of Posttest Only Control Group Design involving eighth grade students of SMP Negeri 1 Seririt. Cluster Random Sampling was assigned to select the sample of this study in which VIIIA Class was assigned as the control group and treated by using storytelling without puppet while VIIIB Class as the experimental group was treated by using storytelling with puppet strategy. Three kinds of instruments were used in this study namely lesson plan, speaking test, and storytelling rubric. Based on the result of the data analysis proves that there is a significant difference on students’ speaking achievement between students who were taught by using storytelling with puppet strategy and those students who were taught by using storytelling without puppet strategy (t= 4.942, df= 62, .p< 0.05). Moreover, the result of the effect size in this study is 0.282. It indicates that storytelling with puppet strategy give a large influence on students’ speaking achievement. Referring to those results, it can be concluded that storytelling using puppet strategy can give significant effect on students’ speaking achievement. Keyword: Puppet Media, Speaking Achievement, Storytelling